Institutional investors, corporate governance and firm performance in an emerging market: evidence from Vietnam - Nguyen Thi Hoa Hong; Tran Khanh Linh (Cogent Economics & Finance, 2023)
This study examines the relationship between institutional investors, corporate governance, and firm performance in Vietnam. The findings on Vietnamese listed companies indicate that while institutional investors are less likely to hold shares of companies with larger board sizes, Chief Executive Officer (CEO) duality, and ultimate control by the state (except for state-owned institutions' perspective), the effect of their ownership on firm performance depends on whether they are pressure-sensitive (grey) or pressure-insensitive (independent) institutions. In Vietnam, independent institutional investors monitor the company and their investment more effectively than grey institutional investors. They can significantly influence management decisions and improve shareholder value. In contrast, grey institutional ownership is either negatively or insignificantly related to firm performance due to conflicts of interest, as they have a potentially related business relationship with the invested companies.
Keywords: G32; G34; 330; corporate governance; firm performance; institutional investors; ownership structure; Vietnam listed companies